APD: Ad Persuasion Dashboard — Insights into Facebook Political Campaign Strategies - Meguellati, Elyas; Civelli, Stefano; Sadiq, Shazia; Demartini, Gianluca (Proceedings of the International AAAI Conference on Web and Social Media, 2026)
This demo presents an interactive dashboard for analyzing persuasive content in political social media advertising. We leverage the APA22 dataset, comprising 56,958 unique Facebook ads from the 2022 Australian Federal Election. The system is powered by PPAsy-XLNet, a lightweight transformer model that achieves state-of-the-art persuasion detection while requiring 86.8% less training data and up to 77.6% fewer parameters than leading ensembles. Our tool allows researchers to visualize campaign dynamics, revealing that highly persuasive ads receive 48.2% more financial investment, peak in volume by 4.8 times before election day, and utilize distinct action-oriented linguistic patterns. This system provides a scalable framework for auditing digital political campaigns.